Reconstruction of soft tissue penile defects due to trauma using inguinal flaps - Hanh, Nguyen Duc; Hung, Pham Ngoc; Phu, Ho Man Truong; Viet, Huynh Anh; Tuan, Nguyen Duong Minh; Chi, Tran Thi Kim (Tạp chí Y học lâm sàng Bệnh viện Trung Ương Huế, 2025)
Background: We present a case of using the external pudendal artery (EPA) flap to cover the soft tissue defects of the penis following multiple trauma with penis shrinkage, corpus spongiosum and urethral injuries. Case report: A 54-year-old male patient was admitted to the hospital with multiple injuries: complex trauma with extensive scrotal and perineal skin loss, soft tissue defects of the penis with corpus spongiosum and urethral injuries, complex and open forearm fracture. The patient underwent emergency surgery to remove scrotal skin, Burry the testis in the subcutaneous pouches in the thigh, Foley sonde was placed over the bladder above the pubic bone and amputate the right hand.After that, the patient was operated on using foreskin flaps to cover corpus spongiosum defects and reconstruct the urethra. However, after about 10 days, the foreskin flap was infected and then necrotic resulting in the soft tissue defects of the penis exposing the urethral.Therefore we decided to perform surgery using the external pudendal artery (EPA) flap to solve that problem. We put sonde foley to shallow urethra and let urine pass out. The cosmetic and functional results of this foreskin-flap have been good. There was no infection, the length of the penis was maintained. The urinary stream has been normal with no urine leakage after surgery. Conclusion: The external pudendal artery flap is a good option for the treatment of patients with penile soft tissue defects. Due to its simplicity, short operation time, easy dissection, good aesthetic outcome. Therefore the external pudendal artery flap is an optimal choice for the treatment of cases of genital soft tissue defects (scrota and penis). Keyword: Inguinal flap, external pudendal artery flap, groin flap.